Analisis Pengaruh Viral Marketing dan Fasilitas Wisata terhadap Keputusan Berkunjung: Studi pada Wisata Religi Masjid al-Jabbar Bandung - Nurlaila Riski; Nur Qurotul Nabila Atiqah; Mutiara Hafsari Hidayat; Farhan Isma Padilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the influence of viral marketing and tourist facilities on the decision to visit the Al-Jabar Mosque in Bandung. In today's digital era, viral marketing plays an important role in influencing the perceptions and interests of potential tourists through content that is quickly distributed on social media. On the other hand, adequate tourist facilities are a crucial factor that can increase satisfaction and encourage visitors to come or return to the Al-Jabar Mosque in Bandung. This research used a quantitative method with a survey approach involving 53 respondents who had visited the Al-Jabar Mosque in Bandung. Data analysis was carried out using multiple linear regression to measure the influence of the independent variables (viral marketing and tourist facilities) on the attachment variable (decision to visit). The research results show that viral marketing and tourist facilities simultaneously and partially have a positive and significant effect on the decision to visit. The aim of this research can be used by the management of the Al-Jabar Bandung Mosque in designing effective promotional strategies and improving the quality of facilities to attract more visitors to worship and travel.